PENGGUNAAN METODE PECS (Picture Exchange Communication System) UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI ANAK AUTIS - Heryati, Euis; RA, Riksma Nurahmi; Ratnengsih, Een (Universitas Pendidikan Indonesia, 2016)
Qualitative disorders of communication are one of the characteristics possessed by children with autism. In children with autism occurred late speech development and the child is trying to communicate nonverbally. In this study tested method of Pecs (Picture Exchange Communication System) is an approach that can be used as an alternative to training communication autistic children. This method adjusts the communication characteristics and uniqueness of children with autism. This research aims to develop an approach to improve the communication skills of children with autism before and after the intervention and the extent of influence methods of Pecs in improving the communication skills of children with autism. The subjects were two autistic children who experience barriers to communication. The method used is an experimental method with the approach of Single Subject Research design A-B-A. The results showed that the mean level of capability to the subject 1 in the communication capabilities at baseline-A (A-1) of 4.7 in the intervention phase obtaining the mean level of 6.5, while the baseline phase-2 (A-2) after a given intervention get the mean level of 10. the early ability subject 2 in communication skills at baseline-A (A-1) of 5.7 in the intervention phase obtaining the mean level of 7.63, whereas the baseline phase-2 (A-2) after being given intervention to get the mean level of 11. the results of the study the two subjects above results in improved communication skills of children with autism in both subjects.Â Keywords : Communication Skills, Autistic, Pecs ( Picture Exchange Communication System)